Fermented vs. Non-Fermented Biofloc: Growth Performance, Biochemical Composition and Water Quality Parameters in Indoor Culture of Goldfish, Carassius auratus - Anitha, R.; Ignus, Akhil; Sukumaran, Mithun (Fishery Technology, 2025)
This study assessed the growth performance, water quality, and biochemical composition of goldfish (Carassius auratus) reared in biofloc technology (BFT) systems. The experiment was conducted over a period of 56 days in 80 L indoor tanks with three treatment groups: control, fermented biofloc, and non-fermented biofloc, each in triplicates. Jaggery served as the carbon source, and biofloc fermentation was achieved using yeast for 24 hours. All treatments were fed a diet containing 36% crude protein (CP) at a daily feeding rate of 5% of the total fish biomass per tank. Juvenile goldfish were stocked at uniform densities with an average initial weight of 0.12±0.01 g and an initial length of 1.12±0.13 cm. The fermented biofloc treatment demonstrated superior growth performance, including a higher specific growth rate (SGR) and a lower feed conversion ratio (FCR) compared to the non- fermented biofloc and control treatments. Protein levels in the fermented biofloc were significantlyhigher than those in the non-fermented biofloc.Additionally, the study revealed adequate levels of essential amino acids (EAA) and non-essential amino acids (NEAA) in the biofloc, highlighting the role of fermentation in enhancing its nutritional quality. These findings suggest that fermented biofloc improves the nutritional profile and promotes the overall well-being and growth of C. auratus.